Employment and the minimum wage: A pluralist approach - Bernhard Schütz (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
When discussing the employment effects of minimum wages, mainstream economic discussion as well as mainstream economics textbooks mainly center around two variations of the neoclassical model: the model of the competitive and the monopsonistic labor market. The current paper offers a different perspective: it provides an assessment of the broader variety of existing theories and develops a new theoretical account which integrates these different views. For the comparison as well as for the later integration of these theories, it draws on an evolutionary economic concept: a micro-meso-macro framework. Here it shows that due to its simple structure and conceptual flexibility, the micro-meso-macro framework is very well suited to the task of integrating these different theoretical visions as well as assessing their evolutionary features. It follows from the analysis that from a theoretical viewpoint, the effect of the minimum wage on employment is indeed ambiguous, which is perfectly in line with the existing empirical evidence.
Keywords: B52; E12; J30; J42; 330